Design and analysis of multi-wavelength diffractive optics - Kim, Ganghun; Domínguez-Caballero, José A.; Menon, Rajesh (Optics express, 2012)
We present an extension of the direct-binary-search algorithm for designing high-efficiency multi-wavelength diffractive optics that reconstruct in the Fresnel domain. A fast computation method for solving the optimization problem is proposed. Examples of three-wavelength diffractive optics with over 90% diffraction efficiency are presented. These diffractive optical elements reconstruct three distinct image patterns when probed using the design wavelengths. Detailed parametric and sensitivity studies are conducted, which provide insight into the diffractive optic's performance when subject to different design conditions as well as common systematic and fabrication errors.